2020
DOI: 10.17501/23621044.2019.2105
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Cultural Values at the Individual Level in Central Africa: A Test of the CVSCALE in Cameroon

Abstract: In order to reduce the risk of failure, it is vital to learn about the different cultures around the world before doing business in other countries. The existing crosscultural business literature dealing with culture assessment methods has been widely criticized (Sharma, 2010). For instance, most studies operationalize personal cultural orientations for individual consumers based on the national scores on Hofstede (1980, 1991) cultural dimensions. In response to these concerns, the Cultural Values Scale (CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The collectivism/individualism, uncertainty avoidance and power distance measures on an individual level were taken from existing research (Djamen et al , 2020; Chew et al , 2022), which is a five-point scale (1 = disagree, 5 = agree). The scales are designed to measure the internalization of Hofstede’s cultural dimensions (all measures see Appendix 2).…”
Section: Methodsmentioning
confidence: 99%
“…The collectivism/individualism, uncertainty avoidance and power distance measures on an individual level were taken from existing research (Djamen et al , 2020; Chew et al , 2022), which is a five-point scale (1 = disagree, 5 = agree). The scales are designed to measure the internalization of Hofstede’s cultural dimensions (all measures see Appendix 2).…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with higher MF are more aggressive and emulous and have higher task motivation than individuals with lower MF (Hofstede, 1980;Tsegaye et al, 2020;Yoo et al, 2011), who are more eager to succeed and perform better (Caputo et al, 2019;Thoring et al, 2014). In comparison, individuals with lower MF pay more attention to cooperation and caring and nurturing for others (Djamen et al, 2020) rather than competition. Moreover, one study demonstrated that individuals with a higher MF were better at acting than designing, thinking and discussing (Thoring et al, 2014).…”
Section: Mf and Anxietymentioning
confidence: 97%